PENGARUH UKURAN PERUSAHAAN, RETURN ON ASSET, RETURN ON EQUITY DAN DEBT TO EQUITY RATIO TERHADAP NILAI PERUSAHAAN PADA IDX GROWTH30 - Jhon Lismart Benget; Belthasar Trito Siahaan (Akuntansi Prima, 2023)
The purpose of this study is to examine the effect company size, return on asset, return on equity and debt to equity ratio on the firm value. The population of this study is the IDX Growth 30 Index which were listed on the Indonesia Stock Exchange in 2018-2021. The results of this study indicate that simultaneously company size, return on asset, return on equity and debt to equity ratio on the firm value affect the firm value. Partially, this study show return on asset, return on equity and debt to equity ratio has a positive and significant effect on the firm value. Company size has no significant effect on the firm value.